2010
DOI: 10.1590/s0036-36342010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of disordered eating and its impact on quality of life among a group of college students in a province of west Turkey

Abstract: 190salud

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
(17 reference statements)
0
7
0
5
Order By: Relevance
“…37 Üniversite öğrencileri ile yapılan diğer çalışmalarda ise sırası ile %4,2, %6,8, %8,8, %14 olarak bildirilmiştir. [38][39][40][41] Bu çalışma ve bildirilen çalışmaların farklı sonuçlarında depresyon yalnızlık ve yeme bozukluğu yaygınlığının bireysel, coğrafik, toplumsal, kültürel, ekonomik ve zaman gibi faktörlerin etkili olabileceği söylenebilir.…”
Section: Bulgularunclassified
“…37 Üniversite öğrencileri ile yapılan diğer çalışmalarda ise sırası ile %4,2, %6,8, %8,8, %14 olarak bildirilmiştir. [38][39][40][41] Bu çalışma ve bildirilen çalışmaların farklı sonuçlarında depresyon yalnızlık ve yeme bozukluğu yaygınlığının bireysel, coğrafik, toplumsal, kültürel, ekonomik ve zaman gibi faktörlerin etkili olabileceği söylenebilir.…”
Section: Bulgularunclassified
“…This data is determined as 13.8% in the study of Tözün et al upon college students in our country. 29 Several studies conducted on various countries are reported that ED frequency among high school students are ranging between 3.5%-28.5%. [29][30][31] These differences may emerge from different measurement methods, from using of different work groups or from cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel to this data, there were some studies that frequency of ED suspicion and number of child in family has no correlation. 29,33 In adolescents, living with family is an important factor on protecting from ED. Therefore, less frequent ED is expected people who living with family.…”
Section: Discussionmentioning
confidence: 99%
“…Al comparar la prevalencia total de ECA positiva en la presente investigación con prevalencias a nivel internacional en poblaciones similares, esta es notoriamente mayor (3,(21)(22)(23). Sin embargo, se debe tener en cuenta que encuestas como la Eating Attitudes Test (EAT40) y Eating Disorder Inventory (EDI), que han sido las más utilizadas a nivel mundial, han mostrado sensibilidad, especifi cidad y valor predictivo positivo más bajos, en especial para el diagnóstico de TCA-NE (24), que es el más frecuente (6).…”
Section: Discussionunclassified
“…De acuerdo a lo anterior, se hace necesaria la ampliación de la información mediante estudios que caractericen mejor algunos aspectos como la relación con las condiciones sociodemográfi cas, imagen corporal y autoestima, los cuales se han visto vinculados estrechamente con estos trastornos (21,22,33). Es necesario considerar a toda la población adolescente como afectada por estos trastornos, ya que existen diferencias significativas entre los presentes hallazgos y los de otros estudios que plantean que el comportamiento de estas patologías podría ser diferente en nuestro medio.…”
Section: Discussionunclassified